SENI JIKEA GEBANO DI BATURIJAL : KAJIAN ETNOGRAFI - Roifah, Fathia; Elmustian, Elmustian; Syafrial, Syafrial (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study discusses the art of jikea gebano in Baturijal sub-district Peranap Indragiri Hulu Regency. Jikea gebano is an art owned by the Baturijal community which is often performed in the from of wedding events, circumcisions, and other official events aimed at entertaining the people of Baturijal. this jikea gebano is played by singing berzanji and 5 rhymes while hitting a drum. As for the objectives to be achieved in this study is to describe the interest and audience response to the jikea gebano performance and describe the relationship between the level of understnding of the text to informant and audience. This study uses a qualitative descriptive method. Data analysis is done by flow technique, which begins with data collection, data reduction, data presentation, and drawing conclusions. The results of the study found that there were many changes that were felt in the past with the present, both in terms of informant, audience, and texst. Seen from informant, there used to be female informant but now there are no more. In terms of the audience, there were a lot of spectator because the jikea gebano is only the only entertainment in Baturijal buat now the demand is reduced because now there are many other entertainment such as single organ, salung dangdut, and kuda lumping. When viewed in terms of text, many of the jikea texts that were sung today have been cut into pieces compared to the past.Key Words: Jikea gebano, Baturijal's artistry.